Framing international trade and chronic disease - Mohindra Katia S; Labonté Ronald; Lencucha Raphael (BMC, 2011)
Abstract There is an emerging evidence base that global trade is linked with the rise of chronic disease in many low and middle-income countries (LMICs). This linkage is associated, in part, with the global diffusion of unhealthy lifestyles and health damaging products posing a particular challenge to countries still facing high burdens of communicable disease. We developed a generic framework which depicts the determinants and pathways connecting global trade with chronic disease. We then applied this framework to three key risk factors for chronic disease: unhealthy diets, alcohol, and tobacco. This led to specific 'product pathways', which can be further refined and used by health policy-makers to engage with their country's trade policy-makers around health impacts of ongoing trade treaty negotiations, and by researchers to continue refining an evidence base on how global trade is affecting patterns of chronic disease. The prevention and treatment of chronic diseases is now rising on global policy agendas, highlighted by the UN Summit on Noncommunicable Diseases (September 2011). Briefs and declarations leading up to this Summit reference the role of globalization and trade in the spread of risk factors for these diseases, but emphasis is placed on interventions to change health behaviours and on voluntary corporate responsibility. The findings summarized in this article imply the need for a more concerted approach to regulate trade-related risk factors and thus more engagement between health and trade policy sectors within and between nations. An explicit recognition of the role of trade policies in the spread of noncommunicable disease risk factors should be a minimum outcome of the September 2011 Summit, with a commitment to ensure that future trade treaties do not increase such risks.